2017
DOI: 10.1073/pnas.1706795114
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated chitin perception in legume roots is functionally separable from Nod factor perception

Abstract: The ability of root cells to distinguish mutualistic microbes from pathogens is crucial for plants that allow symbiotic microorganisms to infect and colonize their internal root tissues. Here we show that and possess very similar LysM pattern-recognition receptors, LYS6/LYK9 and LYR4, enabling root cells to separate the perception of chitin oligomeric microbe-associated molecular patterns from the perception of lipochitin oligosaccharide by theNFR1/LYK3 and NFR5/NFP receptors triggering symbiosis. Inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
171
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(185 citation statements)
references
References 94 publications
11
171
1
2
Order By: Relevance
“…However, attempts to underpin the involvement of NFP in the perception of pathogens showed that M. truncatula possesses other receptors to trigger ROS bursts and defence gene expression (Nars et al ., ; Rey et al ., ). This model is in line with recent elucidation of distinct signalling pathways for chitin triggered immunity and LCO mediated symbiotic responses in M. truncatula roots (Bozsoki et al ., ). In addition, our new data illustrate how these pathways cross‐talk at the level of ROS homeostasis but can function coincidentally.…”
Section: Discussionmentioning
confidence: 97%
“…However, attempts to underpin the involvement of NFP in the perception of pathogens showed that M. truncatula possesses other receptors to trigger ROS bursts and defence gene expression (Nars et al ., ; Rey et al ., ). This model is in line with recent elucidation of distinct signalling pathways for chitin triggered immunity and LCO mediated symbiotic responses in M. truncatula roots (Bozsoki et al ., ). In addition, our new data illustrate how these pathways cross‐talk at the level of ROS homeostasis but can function coincidentally.…”
Section: Discussionmentioning
confidence: 97%
“…Bozsoki et al . () detail evidence that different sets of plant LysM receptor proteins exhibit specificity in being able to perceive rhizobial Nod factors from pathogenic MAMPs. The proteins CERK6 of Lotus and both LYK9 and LYR4 of Medicago do not perceive Nod factors but are instead able to bind pathogenic chitin oligomers, leading to a defensive response by the plant (Bozsoki et al ., ).…”
Section: What Might Influence Differential Plant Responses To Differementioning
confidence: 96%
“…() detail evidence that different sets of plant LysM receptor proteins exhibit specificity in being able to perceive rhizobial Nod factors from pathogenic MAMPs. The proteins CERK6 of Lotus and both LYK9 and LYR4 of Medicago do not perceive Nod factors but are instead able to bind pathogenic chitin oligomers, leading to a defensive response by the plant (Bozsoki et al ., ). In all cases, altered expression of these proteins or mutations to these proteins lead to differences in pathogen susceptibility without any impact on rhizobial nodulation and symbiosis (Bozsoki et al ., ).…”
Section: What Might Influence Differential Plant Responses To Differementioning
confidence: 99%
“…While the results indicated the involvement of partially homologous plasma membrane proteins (RLK1 and NFR) both in defence and symbiotic signalling in plant cells (Kaku et al 2006), Bozsoki et al (2017) revealed that distinct receptor sets respond to chitin and lipochitin oligosaccharides in Lotus japonicus and Medicago truncatula legume roots separating defence from the symbiosis of the roots.…”
Section: Chitin Derived Molecules and Symbiotic Signallingmentioning
confidence: 99%